Cerebral Phaeohyphomycosis: A Case Report (Revista de Medicina Clinica, 2025)
Abstract: Introduction: Phaeohyphomycosis is a fungal infection caused by dematiaceous fungi, which contain melanin in their cell walls. When this type of infection occurs in the brain, it is referred to as cerebral phaeohyphomycosis, with the primary causative agent being the fungus Cladophialophora bantiana. Objective: The aim of this article is to describe the clinical findings in a neuroinfection caused by dematiaceous fungi. Clinical Case: We present the case of a male patient who presented with headache, nausea, vomiting, and altered consciousness. Brain MRI revealed hydrocephalus and increased signal intensity in the third and fourth ventricles and lateral ventricles. The patient underwent a surgical procedure for external ventriculostomy and sample collection, where fungal structures compatible with “aspergilloma” were identified. He was treated with voriconazole, but therapeutic failure occurred, leading to his subsequent death. Post-mortem, a deep mycosis culture from pathology and cerebrospinal fluid samples reported Cladophialophora spp. Conclusions: Cerebral phaeohyphomycosis is a rare condition with high mortality. The presence of suggestive findings in the central nervous system should prompt initiation of aggressive therapeutic regimens that could impact the patient’s prognosis.
Keywords: Cladophialophora bantiana; Meningitis; Fungi